(untitled) (Annals of Medical Research, 2021)
We report a male patient with a diagnosis of peripheral T-cell lymphoma. After a two months of remission, he relapsed and died during the salvage therapy. Peripheral Tcell lymphomas are aggressive and have a poor prognosis. Patients should be evaluated quickly as chemotherapy success rate is low. Bone marrow transplantation should be kept in mind for treatment.